Two potential fields fused adaptive path planning system for autonomous vehicle under different velocities. (June 2021) - Liu, Zhixian; Yuan, Xiaofang; Huang, Guoming; Wang, Yaonan; Zhang, Xizheng
Abstract: Path planning is a basic function for autonomous vehicle (AV). However, it is difficult to adapt to different velocities and different types of obstacles including dynamic obstacle and static obstacle (such as road boundary) for AV. To solve the problem of path planning under different velocities and different types of obstacles, a two potential fields fused adaptive path planning system (TPFF-APPS) which includes two parts, a potential field fusion controller and an adaptive weight assignment unit, is presented in this work. In the potential field fusion controller, a novel potential velocity field is built by velocity information and fused with a traditional artificial potential field for adapting various velocities. The adaptive weight assignment unit is designed to distribute adaptively the weights of two potential fields for adapting different types of obstacles at the same time, including road boundary and dynamic obstacles. The simulation is carried on the Carsim-Matlab co-simulation platform, and the simulation results indicate that the proposed TPFF-APPS has excellent performance for path planning adapting to different velocities and different types of obstacles. Highlights: A path planning system adapting to various velocities is proposed. And this system can also adapt to different types of obstacles. A novel potential velocity field is designed for adapting to various velocities. The weights of different types of obstacles can be distributed adaptively.